Pengaruh Pertumbuhan Ekonomi, Inflasi dan Loan to Deposit Ratio Terhadap Non Performing Loan Pada Bank Umum di Indonesia - Fauziah Zagita Pratama; Ali Anis (Jurnal Kajian Ekonomi dan Pembangunan, 2022)
This study expects to look at the impact of economic growth, inflation, loan to deposit ratio toward non performing loan at commercial banks in Indonesia from 2005 to 2020. This study uses multiple linear regression analysis and found that : (1) Economic growth has a positive but not significant effect on non-performing loans at commercial banks in Indonesia with a significance of 0.7719; (2) Inflation has a negative but not significant effect on non-performing loans at commercial banks in Indonesia with a significance of 0.0852; (3) Loan to deposit ratio has a negative and significant effect on non-performing loans at commercial banks in Indonesia, with a significance of 0.0002; (4) Based on the results of the simultanous test of the effect of the independent variables on the dependent variable, the variables of economic growth, inflation, loan to deposit ratio have a significant effect on non-performing loans in commercial banks in Indonesia by 43%.